Dualism and the big push - Giovanni Valensisi (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
We develop a two-sector model with specific factors, in which agriculture is subject to diminishing returns and market-clearing wages, while increasing returns and efficiency wages prevail in industry. The asymmetric interaction of the two sectors, jointly with the dualistic structure of the labor market, is such that the model may display multiple equilibra and a low-development trap under plausible parametrization. Additionally, parametric increases of sectoral TFP may reduce the basin of attraction of the low-equilibrium and increase the steady state level of capital stock (and wages) for the stable equilibrium of full industrialization.
Keywords: O11; O14; O41; 330; dualism; industrialization; poverty traps; Kaldor-Verdoorn law; Engel's effects